Use of a stakeholder-driven DACUM process to define knowledge areas for food protection and defense - Linton, Richard H.; Nutsch, Abbey L.; McSwane, David; Kastner, Justin; Bhatt, Tejas; Hodge, Sheryl; Getty, Kelly J. K.; Maier, Dirk E.; Kastner, Curtis L.; Chaturvedi, Alok; Woodley, Cynthia (My University, 2011)
One of the important areas of vulnerability that has been repeatedly identified following the events of September 11, 2001 is the potential for an intentional attack on America’s food supply. Despite the importance of equipping professionals to protect our nation’s food supply, educators face a scarcity of information on which to base food protection and defense curricula and training development efforts. This research sought to identify a set of knowledge content areas required by food protection and defense professionals. A Developing A CurriculUM (DACUM) process was employed to create a job task analysis that identified duties, tasks, steps, and associated knowledge, skills, and abilities for this ccupational category. The knowledge areas identified during the DACUM process and validated through a stakeholder survey were used to frame the program for a training workshop and computer simulation in which participants responded to a mock intentional food contamination event. Results of this process can serve as foundational elements that can be shaped by instructional and curricular design experts to create educational programs in food protection and defense for graduate students and in-service professionals.
Keywords: DACUM; Curriculum; Food protection; Food defense; Education; Training; Learning objectives; Computer Simulation; Public Health; Decision-making; Job task analysis; Homeland security